Relevant Issues of Research of Minors’ Antisocial Behavior - Huzik, Oleksandra (Journal of Legal Studies, 2021)
The study of the antisocial behavior of minors is of interest to many scientists: from pedagogues and psychologists to lawyers and criminologists. On the one hand, this has led to important and diverse research detailing the nature, causes, and consequences of deviance among youth. This makes it possible to develop better mechanisms for the prevention of juvenile delinquency, punishment, and resocialization of minor offenders. But on the other hand, this diversity caused contradictory approaches to defining the boundaries of deviance and delinquency, as well as the correlation of these terms. This paper offers an overview of the interdisciplinary scientific discussion on the relationship between delinquency and deviance as types of antisocial behavior, and structures these approaches. It also defines limitations in the field and generates new ideas and directions for future research.  In the second part, we examine the causes of juvenile delinquency, with a particular interest in causes that can be corrected.  Thus, we found that proper upbringing can "treat" not only anti-social attitudes and values, low educational and professional skills of the offender, poor cognitive and interpersonal skills but also innate tendencies to aggression.